ANALISIS TINGKAT KEUTUNGAN USAHATANI SELADA AIR DI KELURAHAN PAGAR WANGI KECAMATAN DEMPO UTARA KOTA PAGAR ALAM - Nirwanto, Nirwanto; Iskandar, Sutarmo; Afriyatna, Sisvaberti (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2016)
The purpose of this study was to determine the level of farm profits watercress and knowing how marketing channels watercress farming. This research carried on in Pagar Wangi villages Dempo Utara PagarAlam city in October to December 2015. The research method used was survey, for sampling in doing simple random simple random sampling and snowball sampling. Data collection methods used in this study were interviews and secondary data that have been determined by using tools like questionnaire that has been prepared in advance. Tabulation of data processing is done then analyzed by descriptive quantitative and qualitative. Research shows that, watercress farming seen from the provision of means of production and marketing. Materials and tools in the farming watercress obtained from buying. Production process at the start of the spreading of seed, fertilizer, maintenance and harvesting.Watercress farming in pagarwangi villages worthy to be pursued. Where R/C on average 3,67. Then stated business is profitable. The marketing of products on the farm watercress to treaders. Merchant and consumer diluents.